Neonatal Gastric Teratoma: A Rare Entity - Bikram Kharga; Vijay Kumar; P. Santosh Prabhu; Sundeep P.T.; Sijo K. John (Journal of Clinical and Diagnostic Research, 2014)
Gastric Teratoma is an extremely rare neoplasm seen in children. It is mostly benign and predominantly seen in males presenting with an abdominal mass. The lung and stomach are very unusual sites for teratoma. Gastric teratoma accounts for less than 1% of all teratomas, less than 100 cases are reported in literature. We report a case in a 20-day-old infant who presented with large abdominal mass; our case is an addition to the few limited known gastric teratomas reported in the world literature.